Faktor-Faktor Serta Upaya Penanaman Budaya Meminta Maaf Di Sekolah - Milah, Midah Hamidatul; Nurishlah, Laesti; Samadi, Mochammad Ramdan (MURABBI, 2024)
Humans are social creatures who need others to survive. As social beings, we often interact, whether with family or friends. Therefore, we need to master social skills to be easily accepted in the environment we live in. The most fundamental social skills are honesty and responsibility. Honesty and responsibility can be seen in a person's behavior when they face problems whether they will be honest and admit their mistakes or not, and whether they will take responsibility for their mistakes or not. Therefore, instilling the culture of apologizing in children from an early age is crucial because it aims to embed the positive values of apologizing in children as they grow up. This research uses a literature study that contains an explanation of the factors and efforts to instill the culture of apologizing in schools.